Evaluation of Post-fracturing Imbibition Oil Displacement Efficiency in Shale Reservoirs - Song, Yutong (International Journal of Electric Power and Energy Studies, 2024)
In order to clarify the imbibition law of shale oil after fracturing with guanidine gum and nano-slickwater, this study quantitatively analyzed the imbibition efficiency of shale core under different time periods of two kinds of fracturing fluids through the imbibition experiment of natural shale core and nuclear magnetic resonance test technology, and preliminarily understood the microscopic crude oil production characteristics of pore throat of shale imbibition. The experimental results show that the imbibition oil removal efficiency of nano-slick water reaches 34.7 %, which is higher than that of guanidine gum fracturing fluid. In the high imbibition efficiency stage of rock samples, within 6 h of the beginning of the experiment, the small pore porosity reaches 20.8 %, the large pore and fracture reach 30 %, and the final imbibition oil displacement rate can reach 31.7% and 39.6 %. The development of micro-fractures and bedding fractures is beneficial to improve the imbibition efficiency. With the extension of time, the imbibition rate gradually decreases, and the utilization degree of pore throat is limited.